Analysis of the Utilization of Office Administration Learning Media - Susanti Lastri; Risma Niswaty; Sitti Hardiyanti Arhas (Journal of Educational Development and Learning (JEDAL), 2024)
Learning outcomes are an indicator of measuring the success of a learning process. To achieve this goal, it is important to observe aspects that influence the course of the teaching and learning process. One of several aspects of factors influencing the learning process is media. The application of media is very important, especially for students, because by using media students can easily digest the lessons being studied. Therefore, it is important to use media to support the implementation of the learning process. The media used certainly follows the developments and demands of the times. The purpose of this study is to understand the use of student learning media at SMKN 5 Jeneponto. This research is qualitative, therefore, to achieve the research objectives, data collection techniques are used, namely observation, interviews and documentation. There are 6 informants, namely 1 teacher and 5 students. Based on the results of the research that has been carried out, utilizing learning media at SMK Negeri 5 Jeneponto has been implemented in various ways that are used by teachers at the school. This can be seen through the benefits obtained through the use of learning media which become a guideline for educators in achieving learning targets, so that teachers can present teaching materials in a structured and supportive manner in presenting materials that are so interesting in order to improve the quality of learning. Learning media is also able to foster students' interest and motivation to learn so that they are able to think and examine the lessons they have received, and in an enjoyable learning situation, students can easily digest the lessons taught so that learning can be carried out well.